Relationship Between Alcohol Consumption and Risky Sexual Behaviors Among Adolescents and Young Adults: A Meta-Analysis - Hyang-Soon Cho; Youngran Yang (Frontiers Media S.A., 2023)
Objectives: Adolescents exposed to alcohol have increased risky sexual behaviors (RSBs); however, the association between alcohol consumption and RSBs has to be systematically and quantitatively reviewed. We conducted a meta-analysis of the literature to systematically and quantitatively review the association between alcohol consumption and RSBs in adolescents and young adults.Methods: We searched for qualified articles published from 2000 to 2020 and calculated pooled odds ratios (ORs) using the random-effect model. We also conducted meta-regression and sensitivity analyses to identify potential heterogeneity moderators.Results: The meta-analysis of 50 studies involving 465,595 adolescents and young adults indicated that alcohol consumption was significantly associated with early sexual initiation (OR = 1.958, 95% confidence interval (CI) = 1.635-2.346), inconsistent condom use (OR = 1.228, 95% CI = 1.114-1.354), and having multiple sexual partners (OR = 1.722, 95% CI = 1.525-1.945).Conclusion: Alcohol consumption is strongly associated with RSBs, including early sexual initiation, inconsistent condom use, and multiple sexual partners among adolescents and young adults. To prevent the adverse consequences of alcohol consumption, drinking prevention programs should be initiated at an early age and supported by homes, schools, and communities.